Co-infection of mice with SARS-CoV-2 and Mycobacterium tuberculosis limits early viral replication but does not affect mycobacterial loads - Baker, Paul J.; Amaral, Eduardo P.; Castro, Ehydel; Bohrer, Andrea C.; Torres-Juárez, Flor; Jordan, Cassandra M.; Nelson, Christine E.; Barber, Daniel L.; Johnson, Reed F.; Hilligan, Kerry L.; Mayer-Barber, Katrin D. (Frontiers in Immunology, 2023)
Viral co-infections have been implicated in worsening tuberculosis (TB) and during the COVID-19 pandemic, the global rate of TB-related deaths has increased for the first time in over a decade. We and others have previously shown that a resolved prior or concurrent influenza A virus infection in Mycobacterium tuberculosis (Mtb)-infected mice resulted in increased pulmonary bacterial burden, partly through type I interferon (IFN-I)-dependent mechanisms. Here we investigated whether SARS-CoV-2 (SCV2) co-infection could also negatively affect bacterial control of Mtb. Importantly, we found that K18-hACE2 transgenic mice infected with SCV2 one month before, or months after aerosol Mtb exposure did not display exacerbated Mtb infection-associated pathology, weight loss, nor did they have increased pulmonary bacterial loads. However, pre-existing Mtb infection at the time of exposure to the ancestral SCV2 strain in infected K18-hACE2 transgenic mice or the beta variant (B.1.351) in WT C57Bl/6 mice significantly limited early SCV2 replication in the lung. Mtb-driven protection against SCV2 increased with higher bacterial doses and did not require IFN-I, TLR2 or TLR9 signaling. These data suggest that SCV2 co-infection does not exacerbate Mtb infection in mice, but rather the inflammatory response generated by Mtb infection in the lungs at the time of SCV2 exposure restricts viral replication.